2016
DOI: 10.1051/e3sconf/20160911002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of structure in the soil-water characteristic curves of two residual soils of granite

Abstract: Abstract. This paper discusses the influence of structure in the soil-water characteristic curves (SWCC) of two residual soils of granite formed in a subtropical environment. One soil has a saprolitic nature (named GrSp) and the other shows lateritic behavior (named GrLt). Both materials occur on a slope which presents a extensive history of landslides in the municipality of São José, Southern Brazil. SWCC of undisturbed and remolded specimens were determined using the filter-paper technique. Undisturbed speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
0
3
0
1
Order By: Relevance
“…Therefore, Grade VI residual soil could retain more moisture with higher matric suction than other materials. Heidemann et al [24] stated that the degree of weathering would not have a consistent effect on SWCCs [25]. Therefore, it is more likely that the parent rock type has a more significant influence on the SWCCs.…”
Section: Soil Water Characteristic Curve (Swcc)mentioning
confidence: 99%
“…Therefore, Grade VI residual soil could retain more moisture with higher matric suction than other materials. Heidemann et al [24] stated that the degree of weathering would not have a consistent effect on SWCCs [25]. Therefore, it is more likely that the parent rock type has a more significant influence on the SWCCs.…”
Section: Soil Water Characteristic Curve (Swcc)mentioning
confidence: 99%
“…In these areas, GRS is widely used as subgrade fill in highway construction for cost-effectiveness. Compared with undisturbed GRS, disturbed GRS usually exhibits strength decline because of residual fabric loss and microstructure change ( 2 , 3 ). Moreover, the high content of sand grains in some GRS favors the formation of higher porosity and permeability ( 4 ), which also favors water intrusion during rainfall.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that SWCC is closely related to the soil’s mineral component, microstructure, stress state, and initial void ratio ( 3 , 12 ). And the influence of stress state can also be attributed to the change in soil void ratio, pore size distribution (PSD), pore shape, and orientation ( 13 , 14 ).…”
mentioning
confidence: 99%
“…Utilizando o método do papel filtro, Heidemann et al (2016), durante a elaboração de Curvas de Retenção de Água, identificaram a relevância dos macro e microporos em dois solos, o primeiro de comportamento laterítico e o segundo saprolitico. Destacaram que, a porosidade é mais relevante em solos lateríticos.…”
unclassified